Physics Online Learning Devices Based on Guided Discovery Model for High School Class X on Momentum and Impulse Material - Eko Mhd Ramadan; Jumadi Jumadi; Dwi Ulan Rahmawati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
This development research aims to develop online physics learning tools based on guided discovery models for high school grade X students with momentum and impulse material and test the feasibility of Physics online learning tools through validator assessments (material experts, material experts) and limited trials by students' responses. Physics online learning tools developed in the syllabus, lesson plans, student worksheets, handouts, and learning media. The average score of validation assessment for the syllabus is 4.81, the lesson plan is 4.72, the student worksheet is 4.64, the handout is 4.57, the media is 4.76, and the media material is 4.66. All in categorized as very worthy. In this study, a limited trial was conducted for 27 students divided into three groups. The average score results student on worksheet one is 4.06, worksheet two is 3.98, and worksheet three is 3.87. All in with categories worthy. The average score result of handout one is 4.04, handout two is 3.96, and handout three is 4.01. All in with worthy category. The results obtained from the Physics online learning tool based on guided discovery models are appropriate for online learning on momentum and impulse material for grade X high school students.